Complete Free-breathing Adenosine Stress Cardiac MRI Using Compressed Sensing and Motion Correction: Comparison of Functional Parameters, Perfusion, and Late Enhancement with the Standard Breath-holding Examination. - Treutlein, Christoph; Wiesmüller, Marco; May, Matthias; Heiß, Rafael; Hepp, Tobias; Uder, Michael; Wüst, Wolfgang (Radiology: Cardiothoracic Imaging, 2019)
Purpose: To compare free-breathing (FB) stress cardiac MRI examinations with the reference standard breath-holding (BH) examination. Materials and Methods: A total of 40 consecutive patients were enrolled prospectively and were examined with 3-T MRI. Functional imaging, perfusion, and late gadolinium enhancement (LGE) sequences were performed in BH and FB by using compressed sensing and in-line motion correction. Left ventricle (LV) and right ventricle (RV) functional parameters in BH and FB examinations were compared by using Bland-Altman plots and linear mixed models. Subjective image quality was assessed with a five-point scale (1 = nondiagnostic, 5 = very good). For perfusion and LGE imaging, diagnostic confidence was rated with a three-point scale (1 = low, 3 = high), and image quality was rated with a five-point scale (1 = nondiagnostic, 5 = very good). The Wilcoxon test was used to compare image quality and diagnostic confidence. Results: Bland-Altman plots showed good agreement for LV and RV functional parameters in BH and FB sequences. Subjective image quality was significantly better with the BH sequences in the LV (P < .01) but was comparable in the RV (P > .99). Scanning time was 218 seconds (range, 130-385 seconds) for cine BH and 16 seconds (range, 11-27 seconds) for cine FB. Extent of perfusion defects, LGE, and diagnostic confidence was comparable between groups. Scanning time was 371 seconds (range, 239-502 seconds) for the LGE BH sequence and 189 seconds (range, 122-286 seconds) for the LGE FB sequence. Conclusion: FB adenosine stress cardiac MRI delivers diagnostic image quality and could represent an alternative for use in patients who are unable to meet the demands of multiple BHs and long examination times.© RSNA, 2019.
EVALuna2:469014